2006
DOI: 10.1002/hed.20442
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cervical esophageal reconstruction for rare esophageal tumors

Abstract: Background. Isolated defects in the cervical esophagus in patients who have not undergone total laryngectomy are uncommon. We report 2 cases of rare esophageal tumors requiring reconstruction of the cervical esophagus after tumor resection.Methods and Results. The patients were a 51-year-old woman with an esophageal granular cell tumor and a 54-yearold woman with an esophageal schwannoma. Both defects were reconstructed with a radial forearm flap. A small subclinical leak developed in 1 patient and healed spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Esophageal schwannomas are exceedingly rare with only a handful of cases reported in the literature [3]. A literature review performed for the past decade, 2005 -2015, revealed a total of 21 cases of which two cases were of concurrent esophageal schwannomas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The surgical approaches to these include four thoracoscopic, six thoracotomy, five cervical approaches, and five esophagectomies or partial esophagectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal schwannomas are exceedingly rare with only a handful of cases reported in the literature [3]. A literature review performed for the past decade, 2005 -2015, revealed a total of 21 cases of which two cases were of concurrent esophageal schwannomas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The surgical approaches to these include four thoracoscopic, six thoracotomy, five cervical approaches, and five esophagectomies or partial esophagectomies.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 11 cases have been reported in the literature, including our 2 cases (table ). [3][4][5][6][7][8][9][10][11] These patients included 4 males and 7 females, aged 10 to 65 years (mean: 45; median: 53). All 11 patients were symptomatic; the most common symptom was dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, in some cases, esophagectomy may be needed. 9 Because of the uncertainty of the preoperative diagnosis of an esophageal mesenchymal tumor, preparations for reconstruction should be made before surgery in every case of CES.…”
Section: Discussionmentioning
confidence: 99%
“…44 For benign tumors, such as schwannomas and granular cell tumors, smaller margins are acceptable to preserve the larynx. However, reconstruction of isolated cervical esophageal defects can be challenging because the resection of a portion of the cricopharyngeus muscle increases the risk of reflux and aspiration.…”
Section: Cervical Esophageal Defects With An Intact Larynxmentioning
confidence: 99%